Influence of ursodeoxycholic acid therapy on levels of fibroblast growth factor 21, adiponectin and biochemical parameters in intrahepatic cholestasis of pregnancy - Kukla, Michał; Kierach, Rafał; Skonieczna, Magdalena; Hudy, Dorota; Dąbrowski, Krzysztof; Menżyk, Tomasz; Derra, Aleksandra; Boroń, Dariusz; Grabarek, Beniamin (Clinical and Experimental Hepatology, 2021)
The aim was to assess whether fibroblast growth factor 21 (FGF-21) and adiponectin influence intrahepatic cholestasis of pregnancy (ICP) pathogenesis and whether ursodeoxycholic acid (UDCA) has an impact on their levels. 50 pregnant women with ICP (ICP PW), 50 with uncomplicated pregnancy (HPW) and 50 healthy nonpregnant women (HW) were included. In ICP PW the first blood sample was drawn at the time of diagnosis, while in HPW it was drawn in the 28th week of pregnancy. The next blood samples were drawn in the 32nd and 36th week of pregnancy and one day after delivery. UDCA was administered when ICP was diagnosed. In ICP PW serum FGF-21 concentration was the lowest at the time of diagnosis with an evident increase after UDCA administration. Serum FGF-21 levels were significantly higher in ICP PW than in HPW from the first to the last measurement. There was a negative association between adiponectin and bile acids (BAs) levels in the later stage of pregnancy in ICP PW. Up-regulated FGF-21 serum levels in ICP patients compared to HPW persisted after delivery, suggesting its role in disease pathophysiology. The negative association between serum adiponectin and BAs of the later stage of pregnancy may suggest its role in regulation of BAs concentration. UDCA exerts a beneficial effect on insulin sensitivity and up-regulates FGF-21 in ICP.